Origanum majorana Essential Oil Lacks Mutagenic Activity in the Salmonella/Microsome and Micronucleus Assays - Andrea dos Santos Dantas; Luiz Carlos Klein-Júnior; Miriana S. Machado; Temenouga N. Guecheva; Luciana D. dos Santos; Régis A. Zanette; Fernanda B. de Mello; João Antonio Pêgas Henriques; João Roberto Braga de Mello (The Scientific World Journal)
The present study aimed to investigate the in vitro mutagenic activity of Origanum majorana essential oil. The most abundant compounds identified by GC-MS were γ-terpinene (25.73%), α-terpinene (17.35%), terpinen-4-ol (17.24%), and sabinene (10.8%). Mutagenicity was evaluated by the Salmonella/microsome test using the preincubation procedure on TA98, TA97a, TA100, TA102, and TA1535 Salmonella typhimurium strains, in the absence or in the presence of metabolic activation. Cytotoxicity was detected at concentrations higher than 0.04 μL/plate in the absence of S9 mix and higher than 0.08 μL/plate in the presence of S9 mix and no gene mutation increase was observed. For the in vitro mammalian cell micronucleus test, V79 Chinese hamster lung fibroblasts were used. Cytotoxicity was only observed at concentrations higher than or equal to 0.05 μg/mL. Moreover, when tested in noncytotoxic concentrations, O. majorana essential oil was not able to induce chromosome mutation. The results from this study therefore suggest that O. majorana essential oil is not mutagenic at the concentrations tested in the Salmonella/microsome and micronucleus assays.